SARS-CoV-2 serology and virology trends in donors and recipients of convalescent plasma. (December 2020) - Dulipsingh, Latha; Ibrahim, Danyal; Schaefer, Ernst J.; Crowell, Rebecca; Diffenderfer, Margaret R.; Williams, Kendra; Lima, Colleen; McKenzie, Jessica; Cook, Lisa; Puff, Jennifer; Onoroski, Mary; Wakefield, Dorothy B.; et al.
Abstract: SARS-CoV-2 has infected millions worldwide. The virus is novel, and currently there is no approved treatment. Convalescent plasma may offer a treatment option. We evaluated trends of IgM/IgG antibodies/plasma viral load in donors and recipients of convalescent plasma. 114/139 (82 %) donors had positive IgG antibodies. 46/114 donors tested positive a second time by NP swab. Among those retested, the median IgG declined (p < 0.01) between tests. 25/139 donors with confirmed SARS-CoV-2 were negative for IgG antibodies. This suggests that having had the infection does not necessarily convey immunity, or there is a short duration of immunity associated with a decline in antibodies. Plasma viral load obtained on 35/39 plasma recipients showed 22 (62.9 %) had non-detectable levels on average 14.5 days from positive test versus 6.2 days in those with detectable levels (p < 0.01). There was a relationship between IgG and viral load. IgG was higher in those with non-detectable viral loads. There was no relationship between viral load and blood type (p = 0.87) or death (0.80). Recipients with detectable viral load had lower IgG levels; there was no relationship between viral load, blood type or death.